Disentangling the Empirical Evidence between Personality, Work Experience, and Improvisation among Middle Management Government Officers (Journal of Business Management and Accounting, 2014)
This  study  examined  the  empirical  association  between  personality  traits,  work experience, and improvisation. Big five personality traits (Extraversion, Agreeableness, Conscientiousness, Neuroticism, and Openness) and individual work experience were the  independent  variables;  whereas  individual  improvisation  was  the  dependent variable. Data were collected from middle management level of government officers from various ministries in Putrajaya, Malaysia. Results revealed that Extraversion and Openness had a significant and positive contribution towards improvisation while other traits (Agreeableness, Conscientiousness, and Neuroticism) did not demonstrate a significant association with improvisation. The findings of this study could contribute to the collective knowledge of management and be useful to both theorists and managers.